(untitled) (Research, Society and Development, 2020)
Depression can lead the individual to present abnormal changes in mental function, which can be understood as a prolongation of negative feelings. The nursing team is among the group most prone to mental health problems, among which depression, as they are in close contact with people, accompany suffering, physical and psychological pain, the expectation of improvement or the decline in the state of health. patient health. This is a bibliographic research with a qualitative approach, with the objective of describing risk factors for depression in the daily life of the nursing team in the hospital. After the association of all descriptors, 132 articles were found, 109 were excluded and 23 were selected. After the reflective reading, three categories emerged: Contributing factors for the depression of the nursing professional and Consequences of depression for the nursing professionals and The nursing team, self-medication and suicide. Depression can also be influenced by nursing professionals with low family income. The lower the pay, the higher the prevalence of depression. The professional, in his daily practice, expects the recognition of those who are close to him, but not always the desirable happens, with feelings of incompetence, incapacity, discouragement, impotence and suicidal ideation. It is concluded that it is relevant to examine the factors that can contribute to stress, which will result in healthy environments and with better working conditions in order to prevent adverse reactions that can have consequences not only on the health and well-being of professionals, but also on professional performance and quality of care provided to the patient.